Changes in Urinary Biomarkers of Organ Damage, Inflammation, Oxidative Stress, and Bone Turnover Following a 3000-m Time Trial - Takaki Tominaga; Sihui Ma; Kaoru Sugama; Kazue Kanda; Chiaki Omae; Wonjun Choi; Shunsuke Hashimoto; Katsuhiko Aoyama; Yasunobu Yoshikai; Katsuhiko Suzuki (MDPI AG, 2021)
Strenuous exercise induces organ damage, inflammation, and oxidative stress. Currently, to monitor or investigate physiological conditions, blood biomarkers are frequently used. However, blood sampling is perceived to be an invasive method and may induce stress. Therefore, it is necessary to establish a non-invasive assessment method that reflects physiological conditions. In the present study, we aimed to search for useful biomarkers of organ damage, inflammation, oxidative stress, and bone turnover in urine following exercise. Ten male runners participated in this study and performed a 3000-m time trial. We measured biomarkers in urine collected before and immediately after exercise. Renal damage markers such as urea protein, albumin, N-acetyl-β-D-glucosaminidase (NAG), and liver-fatty acid binding protein (L-FABP), and an intestinal damage marker, intestine-fatty acid binding protein (I-FABP), increased following exercise (p < 0.05). However, a muscle damage marker, titin N-terminal fragments, did not change (p > 0.05). Inflammation-related factors (IRFs), such as interleukin (IL)-1β, IL-1 receptor antagonist (IL-1ra), IL-6, complement (C) 5a, myeloperoxidase (MPO), calprotectin, monocyte chemoattractant protein (MCP)-1, and macrophage colony-stimulating factor (M-CSF), increased whereas IRFs such as IL-4 and IL-10 decreased following exercise (p < 0.05). IRFs such as tumor necrosis factor (TNF)-α, IL-2, IL-8, IL-12p40, and interferon (IFN)-γ did not change (p > 0.05). Oxidative stress markers, such as thiobarbituric acid reactive substances (TBARS) and nitrotyrosine, did not change following exercise (p > 0.05) whereas 8-hydroxy-2'-deoxyguanosine (8-OHdG) decreased (p < 0.05). Bone resorption markers, such as cross-linked N-telopeptide of type I collagen (NTX) and deoxypyridinoline (DPD), did not change following exercise (p > 0.05). These results suggest that organ damage markers and IRFs in urine have the potential to act as non-invasive indicators to evaluate the effects of exercise on organ functions.